Mitochondrial ATP fuels ABC transporter-mediated drug efflux in cancer chemoresistance - Emily L. Giddings (Nature Portfolio, 2021)
Drug efflux through ABC transporters is a common mechanism leading to chemoresistance in cancer. Here, the authors show that mitochondrial respiration provides ATP to allow ABC transporters activity so mitochondrial respiration inhibition overcomes chemoresistance in preclinical cancer models.